2022
DOI: 10.47065/jtear.v2i4.266
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Customer Trust: A Study on Safety, Ease-of-use, and Perceived usefulness of Herbal Products of Kuku Bima Ener-G

Abstract: People have alternative treatments and treatments through traditional techniques and herbal remedies. They have attitudes and beliefs about herbs to be able to overcome complaints of certain diseases or just treatment of the body. Pharmaceutical companies in the traditional medicine group are growing. This makes the market share more competitive, because there are so many products for indications based on complaints about disease disorders or increasing body vitality. Related to this, it is very important to k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Together with perceived ease of use, PU constitutes a pivotal predictor of users' adoption attitude and intention in the technology acceptance model (TAM). Extensively examined in information systems, education and user research [117,118], PU significantly shapes actual technology usage intention and behavior. Specifically for hedonic systems, PU meets users' expectations for enjoyment, fosters perceived value and promotes usage willingness, fosters perceived value and enhances willingness to use [39].…”
Section: Perceived Usefulnessmentioning
confidence: 99%
“…Together with perceived ease of use, PU constitutes a pivotal predictor of users' adoption attitude and intention in the technology acceptance model (TAM). Extensively examined in information systems, education and user research [117,118], PU significantly shapes actual technology usage intention and behavior. Specifically for hedonic systems, PU meets users' expectations for enjoyment, fosters perceived value and promotes usage willingness, fosters perceived value and enhances willingness to use [39].…”
Section: Perceived Usefulnessmentioning
confidence: 99%
“…This explanation of perceived usefulness is the same as the meaning defined by Davis in (Primanda et al, 2020) Perceived usefulness measures the extent to which a person believes that using a system can increase productivity. According to Kim in (Halizah et al, 2022) mentions that perceived usefulness is a forms of consumer confidence that a product will develop into a better one.…”
Section: Perceived Usefulnessmentioning
confidence: 99%
“…Dehghanpouri, Soltani and Rostamzadeh 47 also revealed that customer trust empirically promotes customer satisfaction and the success of e-CRM of taxpayers of East Azerbaijan province in Iran. Several factors can determine customer trust 3,48 . Ratasuk and Gajesanand 2 found that customer trust can be promoted by food safety and the diminishing of perceived risk in the food delivery business in Bangkok.…”
Section: Customer Trustmentioning
confidence: 99%